Exploring Critical Thinking For Secondary Level Students In Chemistry: From Insight To Practice - Acharya, Kamal Prasad (Journal of Advanced College of Engineering and Management, 2018)
This article examines hands-on activities based on improvisation of low cost and no cost materials that have direct and indirect impacts on critical thinking practices in secondary science classrooms in Nepal. It also tries to explore the science teachers’ activities for the development of critical thinking practices in chemistry for the secondary school students. Meanwhile, the collaborative and the socio‐cultural theoretical dimensions have been taken as the conceptual bases for this study. This study has highlighted the major conceptual and methodological issues in identifying, assessing and exploring critical thinking as well as the implication of chemistry education for the exploration of children's creative and critical thinking. Based on the qualitative research approach, this study used classroom observation and an interview with the students as the tools to pursue the research objectives. There is a great role of hands-on activities to foster the critical thinking in chemistry in an informal class setting.Journal of Advanced College of Engineering and Management, Vol. 3, 2017, Page: 31-39